IMPLEMENTASI UNDANG-UNDANG CIPTA KERJA TERHADAP KESEJAHTERAAN PEKERJA STUDI KASUS DI TOKO KOPERASI TEKAD MANDIRI PONDOK PESANTREN TEBUIRENG - Thoha Bisyri; Rosandi Firmawan; Resika Triani Putri (JOURNAL SAINS STUDENT RESEARCH, 2024)
This research aims to evaluate the implementation of the Job Creation Law in improving the welfare of workers at the Tekad Mandiri Cooperative Shop, Pondok Pesantren Tebuireng, Jombang, which is a cooperative-based small business. This research uses a qualitative descriptive approach with data collection techniques through interviews, observation and documentation. The research results show that although the Job Creation Law offers flexibility in wages and working hours, small cooperatives such as the Tekad Mandiri Cooperative Shop face difficulties in meeting regional minimum wage (UMR), social security and other benefits. Budget limitations are the main obstacle in implementing this policy. In addition, this law is considered more relevant for large companies that have greater financial capacity, while small cooperatives feel burdened by its implementation. This research also found that without additional support from the government, small businesses such as cooperatives have difficulty meeting labor standards set by the Job Creation Law. Based on these findings, this research recommends the need for policy adjustments and government support for small businesses in implementing the Job Creation Law, so that they can encourage worker welfare without burdening the financial aspects of cooperatives.